2022
DOI: 10.3389/fmicb.2022.790189
|View full text |Cite
|
Sign up to set email alerts
|

Tree Species Diversity and Forest Edge Density Jointly Shape the Gut Microbiota Composition in Juvenile Great Tits (Parus major)

Abstract: Despite the microbiome’s key role in health and fitness, little is known about the environmental factors shaping the gut microbiome of wild birds. With habitat fragmentation being recognised as a major threat to biological diversity, we here determined how forest structure influences the bacterial species richness and diversity of wild great tit nestlings (Parus major). Using an Illumina metabarcoding approach which amplifies the 16S bacterial ribosomal RNA gene, we measured gut microbiota diversity and compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Only nestling's, not adult's, gut microbiota varied in response to woodland type (Table 3). This is not surprising given microbial community assembly theory (Costello et al, 2012;Coyte et al, 2021) where source microbes vary according to the external environment (e.g., diet, nesting material, habitat) (Chen et al, 2020;Goodenough et al, 2016;Goossens et al, 2022;Koenig et al, 2010) and compete for available niches as the host physiological environment develops (Costello et al, 2012). Given that nestlings immune and digestive systems are probably still developing (Caviedes-Vidal & Karasov, 2001;Stambaugh et al, 2011) and their microbiota is still being established, it is likely that the early microbiota contain transient environmental strains that may be replaced by more stable resident bacteria as the birds mature, similar to the distinct stages found in human infant microbiota development (Stewart et al, 2018).…”
Section: Environment and Agementioning
confidence: 99%
See 1 more Smart Citation
“…Only nestling's, not adult's, gut microbiota varied in response to woodland type (Table 3). This is not surprising given microbial community assembly theory (Costello et al, 2012;Coyte et al, 2021) where source microbes vary according to the external environment (e.g., diet, nesting material, habitat) (Chen et al, 2020;Goodenough et al, 2016;Goossens et al, 2022;Koenig et al, 2010) and compete for available niches as the host physiological environment develops (Costello et al, 2012). Given that nestlings immune and digestive systems are probably still developing (Caviedes-Vidal & Karasov, 2001;Stambaugh et al, 2011) and their microbiota is still being established, it is likely that the early microbiota contain transient environmental strains that may be replaced by more stable resident bacteria as the birds mature, similar to the distinct stages found in human infant microbiota development (Stewart et al, 2018).…”
Section: Environment and Agementioning
confidence: 99%
“…Exposure to different environmental pools of microbes are probably important, such as those in the air, soil or diet (Grond et al, 2017; Kartzinel et al, 2019; Liddicoat et al, 2020; Ren et al, 2017). The link with diet is especially likely to explain why gut microbiota can vary with habitat (Drobniak et al, 2021; Goossens et al, 2022; Teyssier, Rouffaer, et al, 2018). Vegetation and diet can also vary dramatically within habitats, for example with respect to edge effects (Chen et al, 1992; Wilkin et al, 2007), although it is unknown whether individual microbial communities are affected by these fine‐scale processes.…”
Section: Introductionmentioning
confidence: 99%
“…At the phylum level, the gut microbiome was dominated by Firmicutes and Proteobacteria, which have also been found to predominate among swimming birds (e. Dong et al, 2019;Gu and Zhou, 2021;Zhang et al, 2021a). Furthermore, it has also been demonstrated that the fecal microbiome of Asian crested ibises (Nipponia nippon) (Zhu et al, 2021) and great tits (Parus major) (Goossens et al, 2022) is dominated by Firmicutes and Proteobacteria. Firmicutes have been found in some avian species to help the host break down complex carbohydrates, polysaccharides, and fats (Turjeman et al, 2020), thus improving the ability of hosts to absorb energy and nutrients from daily food.…”
Section: Discussionmentioning
confidence: 94%
“…diet, nesting material, habitat) (C.-Y. Chen et al, 2020; Goodenough et al, 2016; Goossens et al, 2022; Koenig et al, 2010) and compete for available niches as the host physiological environment develops (Costello et al, 2012). Diet has a strong seasonal component during this time, as the availability of food items changes throughout the breeding season and varies with habitat type, habitat quality and parental preferences (Wilkin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Individual variation in the gut microbiota may be influenced by exposure to different environmental pools of microbes, for example, those in the air, soil or diet (Grond et al, 2017; Kartzinel et al, 2019; Liddicoat et al, 2020; Ren et al, 2017). The link with diet, in particular, is likely to explain why gut microbiota can vary with habitat type (Drobniak et al, 2021; Goossens et al, 2022; Teyssier, Rouffaer, et al, 2018). Vegetation and diet can also vary dramatically within habitats, for example with respect to edge effects (J.…”
Section: Introductionmentioning
confidence: 99%